Lobe of origin of lung cancer among asbestos-exposed patients with or without diffuse interstitial fibrosis. - Karjalainen, Antti; Anttila, S.; Heikkila, L.; Kyyronen, P.; Vainio, Harri (Scandinavian Journal of Work, Environment & Health, 1993)
The effect of asbestos exposure and asbestos-associated fibrosis on the lobe of origin of lung cancer was studied among 108 lung cancer patients. The asbestos-exposed patients had significantly more lower lobe tumors than the unexposed patients. Similar results were obtained when occupational history or lung fiber concentration was used as an indicator of past occupational exposure to asbestos. The predominance of lower lobe tumors occurred even among exposed patients with no histological signs of asbestosis in their lung specimens. Both bronchial and peripheral cancers showed a lower lobe predominance among the exposed patients. Smoking history did not affect the lobar distribution of the tumors. No significant differences occurred for the histological cell types of the tumors between the exposed and unexposed patients. Patients with asbestosis had, however, more adenocarcinomas than the unexposed patients. The results indicate that asbestos may increase the risk of lung cancer even in the absence of asbestosis.